2023
DOI: 10.3389/fphys.2023.1191927
|View full text |Cite
|
Sign up to set email alerts
|

Association between the SLC6A11 rs2304725 and GABRG2 rs211037 polymorphisms and drug-resistant epilepsy: a meta-analysis

Abstract: Background: Previous studies have shown that SLC6A11 and GABRG2 are linked to drug-resistant epilepsy (DRE), although there have been conflicting results in the literature. In this study, we systematically assessed the relationship between DRE and these two genes.Methods: We systematically searched the PubMed, Embase, Cochrane Library, Web of Science, Google Scholar, Wanfang Data, CNKI, and VIP databases. To clarify whether heterogeneity existed between studies, tools such as the Q-test and I2 statistic were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Some studies have shown that SPOCD1 [577], DRD3 [578], DOCK5 [579], SLCO6A1 [305], HTR2C [580], OTX2 [581], LMX1A [582], NR2E1 [319], GPR78 [323], RORB (RAR related orphan receptor B) [583], NTNG2 [326], PRR5-ARHGAP8 [584], CACNA2D4 [585], SLC1A2 [586], CUX2 [587], KCNH7 [588] and ACAN (aggrecan) [335] plays a certain role in bipolar disorder. The altered expression of ABCG2 [589], LAMC3 [590], CACNA1A [591], COL6A2 [592], SLC13A5 [593], GABRA2 [594], SCN5A [160], KCNQ5 [595], SLC1A2 [596], TRPC3 [597], GABRA4 [598], SLC6A11 [599], KCNQ5 [600] and SLCO5A1 [601] are associated with epilepsy. In summary, DEGs involved in GO term and REACTOME pathway were more likely related to schizophrenia and might be important targets in schizophrenia therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that SPOCD1 [577], DRD3 [578], DOCK5 [579], SLCO6A1 [305], HTR2C [580], OTX2 [581], LMX1A [582], NR2E1 [319], GPR78 [323], RORB (RAR related orphan receptor B) [583], NTNG2 [326], PRR5-ARHGAP8 [584], CACNA2D4 [585], SLC1A2 [586], CUX2 [587], KCNH7 [588] and ACAN (aggrecan) [335] plays a certain role in bipolar disorder. The altered expression of ABCG2 [589], LAMC3 [590], CACNA1A [591], COL6A2 [592], SLC13A5 [593], GABRA2 [594], SCN5A [160], KCNQ5 [595], SLC1A2 [596], TRPC3 [597], GABRA4 [598], SLC6A11 [599], KCNQ5 [600] and SLCO5A1 [601] are associated with epilepsy. In summary, DEGs involved in GO term and REACTOME pathway were more likely related to schizophrenia and might be important targets in schizophrenia therapy.…”
Section: Discussionmentioning
confidence: 99%